LANGUAGE INTERFERENCE: OVERVIEWING THE FUNDAMENTALS (Scientific Conference on Multidisciplinary Studies, 2025)
In the presented article below based on the works of the scientists in the field of linguistics in general and language contact in particular we intend to discuss and overview the phenomenon of language interference also known as linguistic interference, cross linguistic interference or transfer. While making literature review on foreign, Russian and Kazakhstani linguists’ outcomes some basic notions have been revealed and determined such as the definition, the essence,and the classifications. Language interference is often treated as the collaboration of two or sometimes more language systems that outcomesin the insight of norms of one language into another within the process of language contacts on the whole. In most cases languageinterference emerges in the second language acquisition process.Scholars view such a phenomenon from different prospectives. It tends to occur as a negative process mostly. Although in some caseslanguage interference can be regarded as a positive influence. Along with these opposite viewpoints there is a neutral opinion on it.